Micronuclei Formation and Comet Assay in Women with Polycystic Ovarian Syndrome (PCOS) - AL-Ahmed , Hazim Ismail Abdul-Bari; Mahood , Rasha Abdul-Hussein; Abdul-Fattah , Shaimaa Yousif (Iraqi Journal of Science, 2022)
Recently the polycystic ovary syndrome (PCOS) has been linked with DNA damage and genomic instability. Amis of this study to evaluated some parameters of genetic instability such as micronuclei and comet assay score in women with PCOS. Genotoxicity and cytotoxicity of DNA damage were evaluated by measured of micronuclei and comet assay in 25 patients with PCOS and 15 normal menstrual women as control group. The results showed higher significant differences in the level of micronuclei and comet score in patients with PCOS compared with normal women. We concluded that, the genetic instability more occurred in patients with PCOS when compared with control group.Keywords: MN, comet assay, PCOS